2016
DOI: 10.2139/ssrn.2766242
|View full text |Cite
|
Sign up to set email alerts
|

Major Challenges Facing Small and Medium-Sized Enterprises in Asia and Solutions for Mitigating Them

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 18 publications
1
102
2
1
Order By: Relevance
“…Many MSMEs are not bankable, because generally MSMEs do not have good bookkeeping, whereas good bookkeeping is one of the requirements to obtain financing from the bank. The same thing was also put forward by Yoshino and Taghizadeh (2016), Tambunan (2008), Bellefleur, et.al. (2012).…”
Section: Introductionsupporting
confidence: 57%
“…Many MSMEs are not bankable, because generally MSMEs do not have good bookkeeping, whereas good bookkeeping is one of the requirements to obtain financing from the bank. The same thing was also put forward by Yoshino and Taghizadeh (2016), Tambunan (2008), Bellefleur, et.al. (2012).…”
Section: Introductionsupporting
confidence: 57%
“…Yoshino and Taghizadeh-Hesary (2016) reported the following as the main reasons for the retardation of SMEs growth. These are (a) absence of finance, (b) absence of appropriate databases, (c) low level of R&D expenditures, and (d) inadequate use of information technology.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
“…H5 = Lack of external funding will relate negatively to SMEs WTI Information flow: Another challenge that affects small and medium enterprises is lack of access to reliable information. Businesses cited in Africa suffer immensely from inadequate business information from both service providers and government institutions (Chopra et al, 2007;Oshikoya & Hussian, 2007;Hamisi, 2010;Nyang'au 2013;Kamunge et al, 2014;Yoshino & Taghizadeh-Hesary, 2016;Emezie 2017). The major problem arises from poor environmental information emanating from the business fraternity due to undeveloped communication infrastructure and technological inadequacies (Kamunge et al, 2014;Oshikoya & Hussain, 2007).…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
“…Yoshino and Taghizadeh-Hesary [11] revealed that SMEs made up more than 98% of Asian businesses providing two out of three private sector jobs. The authors also emphasised that functional support is vital for the sector.…”
Section: Literature Reviewmentioning
confidence: 99%